Turbulent flow and dispersion inside and around elevated walkways. (15th April 2020) - Duan, G.; Brimblecombe, P.; Chu, Y.L.; Ngan, K.
Abstract : The influence of an elevated walkway on turbulent flow and dispersion inside a street canyon is investigated numerically with large-eddy simulation (LES). Different walkway designs and elevations are examined for a unit-aspect-ratio street canyon and an external wind perpendicular to the canyon axis. In place of a principal vortex extending through the canyon, smaller primary vortices appear above the walkway lid or below the walkway deck, in accord with the effective aspect ratio of the upper and lower regions. The mean flow decelerates below the deck and the turbulence kinetic energy (TKE) increases around the walkway structure for all configurations. Ventilation mechanisms for a pollutant emitted by a ground-level area source are qualitatively altered. Consequently mean concentrations at the pedestrian and walkway levels may increase by up to 20 % and 30 %, respectively. The velocity and pollutant statistics show a complicated dependence on the walkway design; this dependence is determined in part by interactions between the mean flow and turbulence. Highlights: A distinct canyon microenvironment is established by the presence of an elevated walkway. The existence of coherent vortices above and below the walkway structure is in accord with the dynamics of 2D street canyons. Dispersion routes are qualitatively altered due to the diversion of streamlines and the increase of TKE around the walkway. Displacing pedestrians from the street level to an elevated walkway lowers pollutant exposure.